2007
DOI: 10.1111/j.1365-2591.2007.01266.x
|View full text |Cite
|
Sign up to set email alerts
|

Fracture strength of bovine incisors after intra‐radicular treatment with MTA in an experimental immature tooth model

Abstract: The use of MTA + metallic post as an intra-radicular reinforcement treatment increased the resistance to fracture of weakened bovine teeth in an experimental immature tooth model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
131
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(151 citation statements)
references
References 44 publications
7
131
0
5
Order By: Relevance
“…A thin film of polyether impression material was used to coat the surface of the roots to simulate periodontal ligament (21) and each sample was placed coronalapically inside a custom-made epoxy resin holder to streamline further co-registration processes. The image stacks of the specimens after preparation were rendered and co-registered with their respective preoperative data sets using the affine algorithm of the 3D Slicer 4.4.0 software (available from http://www.slicer.org).…”
Section: Root Canal Preparationmentioning
confidence: 99%
“…A thin film of polyether impression material was used to coat the surface of the roots to simulate periodontal ligament (21) and each sample was placed coronalapically inside a custom-made epoxy resin holder to streamline further co-registration processes. The image stacks of the specimens after preparation were rendered and co-registered with their respective preoperative data sets using the affine algorithm of the 3D Slicer 4.4.0 software (available from http://www.slicer.org).…”
Section: Root Canal Preparationmentioning
confidence: 99%
“…4,8 The use of intraradicular posts and prosthetic reconstruction has been recommended in cases with large crown destruction 11 to increase root strength. [12][13][14][15] In teeth with IR, it has been evidenced that root FS increases when intraradicular posts and luting agents are employed. 12 The cementation may be performed with resin composite, 13 glass ionomer cement 16 and resin cements 17 aiming to a greater adhesion between post and dentine wall of root canal.…”
Section: 10mentioning
confidence: 99%
“…Each specimen was positioned into a cylindrical device as described by Melo et al 2005 29 and Bortoluzzi et al 2007, 15 which enables an angle of 135º in relation to the long axis of the tooth. The obtained data of fracture strength were statistically evaluated by using one-way analysis of variance (1-way ANOVA), and the Tukey test (α = 0.05).…”
Section: Fracture Strength Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies reported that when MTA is used for orthograde root canal filling, its sealing ability is inferior 15) or superior 16) to that of gutta-percha. A few studies have shown that MTA is an effective root reinforcement material 17,18) . However, one of the drawbacks of MTA is the difficulty of its handling.…”
Section: Introductionmentioning
confidence: 99%